2019
DOI: 10.3171/2018.4.jns173080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in the surgical treatment of intracanalicular primary optic nerve sheath meningiomas

Abstract: OBJECTIVEAlthough meningiomas frequently involve the optic nerve, primary optic nerve sheath meningiomas (ONSMs) are rare, accounting for only 1% of all meningiomas. Given the high risk of vision loss with these tumors, surgical intervention is seldom considered, and radiation or observation is commonly applied. Here, the authors describe the visual outcomes for a series of patients who were treated with surgery aiming at maximal tumor resection and highlight their prognostic factors.METHODSThe authors retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…26 Rassi et al reported that patients with good preoperative vision and CSF flow in the optic sheath had better chances of a favorable outcome than those with poor vision. 27 In our series, ONSM was diagnosed on average 16 months after patients first noticed changes in their vision or reported symptoms related to ONSM. There was no difference in delay in diagnosis between patients with or without documented visual acuity.…”
Section: Dovepressmentioning
confidence: 82%
See 1 more Smart Citation
“…26 Rassi et al reported that patients with good preoperative vision and CSF flow in the optic sheath had better chances of a favorable outcome than those with poor vision. 27 In our series, ONSM was diagnosed on average 16 months after patients first noticed changes in their vision or reported symptoms related to ONSM. There was no difference in delay in diagnosis between patients with or without documented visual acuity.…”
Section: Dovepressmentioning
confidence: 82%
“… 26 Rassi et al reported that patients with good preoperative vision and CSF flow in the optic sheath had better chances of a favorable outcome than those with poor vision. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective analysis, the predictive factors that hold a great statistically significance were symptoms' duration, mild pre-operative visual affection, tumors less than 3cm, absence of arterial encasement and finally gross total resection [4,6,9,[11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Gross total resection was achieved in 19/24 (79.1%) of cases. Gross total resection is a common prognostic factor for visual recovery in many literatures [5,6,12,24,25] . This can be emphasized as Simpson GII resection provided the maximum decompression effect to optico-chiasmatic apparatus [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation